A study on the Muallaf position in relation to the management of inheritance in Malaysia - Drs Nasrul, Muhammad Amrullah; Mohd Alam Shah, Nurin Athirah; Mohd Salim, Wan Noraini (USIM Education & Skills Development Sdn Bhd (UESSB), 2024)
The management of inheritance is among the things that need to be prioritised by the living to ensure that the estate shall be distributed accordingly to the deserved beneficiaries. Presently, a large part of Malaysian society recognises the significance of inheritance, with specific legal rules that governing Muslims and non-Muslim subjects. For Muslims, the law of Faraid dictates over the distribution of inheritance, while non-Muslims follow the Distribution Act of 1958 and the provision stated in the will of the deceased. The divergence in legal frameworks is evident in the management and distribution of inheritance between these two groups since each is subject to a different set of laws. However, complications as to inheritance management arise when non-Muslims convert to Islam (Muallaf), particularly when the deceased leaves non-Muslim heirs. This study aims to look into the position of Muallaf under the subject of inheritance, covering both civil and syariah legal systems. This study adopts a qualitative approach, utilizing library-based research on relevant materials such as statutory provisions, case laws, textbooks, journal articles, newspapers, conference proceedings, and seminar papers. The findings reveal challenges in resolving inheritance issues involving Muallaf, leading to potential conflicts between the Syariah Court and the Civil Court. To address this, the implementation of clear guidelines for handling Muallaf cases is recommended to promote harmony in inheritance laws between Muslims and non-Muslims.